2020
DOI: 10.1111/irv.12805
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of influenza virus infections confirmed by serology in children and adult in a suburb community, northern China, 2018‐2019 influenza season

Abstract: Background In mainland China, seasonal influenza disease burden at community level is unknown. The incidence rate of influenza virus infections in the community is difficult to determine due to the lack of well‐defined catchment populations of influenza‐like illness surveillance sentinel hospitals. Objectives We established a community‐based cohort to estimate incidence of seasonal influenza infections indicated by serology and protection conferred by antibody titers against influenza infections during 2018‐20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 23 publications
2
17
2
Order By: Relevance
“…Noticeably, our study has identified not only substantial outpatient burden (range: 2.7–19.8%) in people aged ≥60 years but also high risks of infections with influenza indicated by serology in the age group. Although the wintertime influenza season in 2019–2020 ended earlier, the incidence rate of infection with influenza virus indicated by serology in people aged ≥60 years reached 25% (95% CI: 21–30%), which was slightly higher than that (21%; 95% CI: 17–25%) in adults 18–59 years in another serological cohort study conducted in Shanxi Province in 2018–2019 20 . Contrary to other studies in other countries and China, our study indicated that the influenza‐associated outpatient burden in people aged ≥60 years was higher than those in adults under 60 years 8,15–18 .…”
Section: Discussionmentioning
confidence: 79%
“…Noticeably, our study has identified not only substantial outpatient burden (range: 2.7–19.8%) in people aged ≥60 years but also high risks of infections with influenza indicated by serology in the age group. Although the wintertime influenza season in 2019–2020 ended earlier, the incidence rate of infection with influenza virus indicated by serology in people aged ≥60 years reached 25% (95% CI: 21–30%), which was slightly higher than that (21%; 95% CI: 17–25%) in adults 18–59 years in another serological cohort study conducted in Shanxi Province in 2018–2019 20 . Contrary to other studies in other countries and China, our study indicated that the influenza‐associated outpatient burden in people aged ≥60 years was higher than those in adults under 60 years 8,15–18 .…”
Section: Discussionmentioning
confidence: 79%
“…The cohort, including 203 children 5–17 years old and 413 adults 18–59 years old, was enrolled in the pre– and post–flu season of 2018/2019. The overall infection incidence based on serological tests was reported in our previous work ( Xu et al, 2021 ). The research protocol was approved by the institutional review board of the National Institute for Viral Disease Control and Prevention, Chinese Centers for Disease Control and Prevention, and written informed consent was obtained from the participants.…”
Section: Methodsmentioning
confidence: 91%
“…The global head of HA is highly variant, and NA is relatively conserved. For HI, the assay is conventionally used to characterize antigenicity, diagnosis, or vaccine evaluation ( Schulman and Kilbourne, 1969 ; Eichelberger and Wan, 2015 ; Xu et al, 2021 ), while it is limited in the current seasonal H3N2 virus experiments. Anti-NA Abs could alleviate clinical severity by inhibiting viral release from infected cells ( Schulman, 1969 ; Couch et al, 2013 ; Eichelberger and Wan, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A three-year prospective study carried out in Hong Kong estimated that the cumulative infection incidence in the subjects enrolled (aged between 5 and 17) was 59% during the first wave of H1N1 in 2009, then 7%, 14%, 20%, and 31% during the subsequent epidemics of H3N2 (2010), H1N1pdm09 (2011), B (2012) and H3N2 (2012), respectively [ 5 ]. Following the same approach, a study on the varying incidence of the influenza virus among children (203 subjects enrolled, aged between 5 and 17) and adults (413 subjects enrolled, aged between 18 and 59), based on antibody testing, showed an overall incidence rate of seasonal influenza of 31% and 21% in the two groups [ 90 ]. Several prototypes have been designed to describe how school closure might lead to a reduction in the incidence peak of the influenza virus pandemic; an example of this is the study by Ferguson et al [ 91 ], pointing to a drop by as much as 40%.…”
Section: The Influenza Virus and Decision-making During The Covid-19 Pandemicmentioning
confidence: 99%